2009
DOI: 10.4103/0301-4738.55070
|View full text |Cite
|
Sign up to set email alerts
|

Effective pupil dilatation with a mixture of 0.75% tropicamide and 2.5% phenylephrine: A randomized controlled trial

Abstract: Purpose:To compare the efficacy in pupil dilatation between a mixture containing 0.75% tropicamide and 2.5% phenylephrine and the alternate application of 1% tropicamide and 10% phenylephrine eye drops.Material and Methods:Patients requiring pupil dilatation were randomized to receive one drop of the mixture every 10 min for four times or our standard application of one drop of 1% tropicamide alternating with one drop of 10% phenylephrine every 10 min for two cycles. Pupil size was measured under bright light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
0
12
0
3
Order By: Relevance
“…A mixture of reduced concentration of tropicamide and phenylephrine in patients with darkly pigmented irides was reported to be sufficiently effective for pupillary dilatation in indirect ophthalmoscopy 4, 5. This study also showed that the lower concentration of dilating drops in the TPD protocol neither compromised the average gain in pupillary increment nor the mean mydriatic rate at the 60 min mark.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A mixture of reduced concentration of tropicamide and phenylephrine in patients with darkly pigmented irides was reported to be sufficiently effective for pupillary dilatation in indirect ophthalmoscopy 4, 5. This study also showed that the lower concentration of dilating drops in the TPD protocol neither compromised the average gain in pupillary increment nor the mean mydriatic rate at the 60 min mark.…”
Section: Discussionmentioning
confidence: 57%
“…However, these preservatives have been linked to unwanted ocular surface side effects, such as stinging, redness and corneal punctate epithelial erosion. A combination of pre-operative eye drops in one bottle may not only reduce the frequency of multiple eye drop administrations but may also reduce the ocular and systemic complications 3, 4, 5. There were some reports on the efficacy and safety of a combination of tropicamide and phenylephrine,4, 5, 6 but there is no report on a combination of tropicamide, phenylephrine and diclofenac.…”
Section: Introductionmentioning
confidence: 99%
“…6 Selama ini para ahli telah merekomendasikan penggunaan kombinasi tropikamid dan efinefrin untuk melebarkan pupil. 7,8 Namun, kombinasi kedua obat ini kadang dirasakan kurang efektif pada pasien retinopati diabetika akibat keadaan neuropati yang juga terjadi. Oleh karena itu, perlu dicari obat tambahan yang dapat membantu penetrasi obat sehingga efek midriasis akan lebih mudah dicapai.…”
Section: Pendahuluanunclassified
“…Secara histologis, otot ini dibentuk dari serabut otot polos yang berhubungan dengan stroma iris dan otot dilator pupil. 8 Pada keadaan normal, pupil akan bereaksi terhadap intensitas cahaya. Pupil akan berdilatasi dan konstriksi sebagai reaksi dari perubahan intensitas cahaya yang akan dapat merangsang sistem simpatetik dan parasimpatetik dari pupil.…”
Section: Pembahasanunclassified
See 1 more Smart Citation